Penyakit Tangan Kaki dan Mulut di Praktik Swasta - Sutaryo Sutaryo (Berita Kedokteran Masyarakat (BKM), 2003)
Background: Hand Foot and Mouth Disease (HFMD) is caused by the Coxsackie's and enteroviruses. The disease has spread out in South East Asia. There was no report of this disease inYogyakarta until 2000. This was the first report of HFMD in Yogyakarta. Methods: During 8 months from May 1, 2001 to December 31, 2001, 42 cases were examined in a private practice.Results: There were 42 cases of the disease during 8 months. The highest number of cases (21 cases) was found in July 2001. Mostly cases were found in children under 5 years old especially in those 13-24 months of age. The ratio between boys and girls was 3:2. The clinical manifestations included fever about 1-3 days, enanthem, exan-them, vesicle, and ulcer in hands, foot, and nausea.Conclusions: All of the cases can be cured by symptomatic treatment and there is no complication of the disease. It is important for Yogyakarta special province to keep far from the disease by the prevention program. Keywords: HFMD, enterovirus, children